Lost in the supermarket –The Traditional Museums Challenges (Cadernos de Sociomuseologia, 2010)
“I’m all lost in the supermarket. I can no longer shop happily. I came in here for the special offer. A guaranteed personality”. The song by The Clash, released in 1979, “Lost in the Supermarket” describes the protagonist struggle to deal with an increasingly commercialized society and the depersonalization of the world around him. The song speaks about alienation and the feelings of disillusionment and lack of identity that come through modern society.  There are different ways which one can decrease those feelings and promote knowledge, self-awareness and understanding. The museum, when used with all its potential, is one of the ways. But how to do that? That is the question museum professionals ask themselves. This paper analyses how the traditional museum can use the new museology concepts, and the challenges of this approach, to become a vehicle for community development and empowerment, diminishing the feelings sang by The Clash.